The Fantasy Economy: Neoliberalism, Inequality, and the Education Reform Movement - Wills, Jocelyn (Radical Teacher, 2025)
A review of Neil Kraus's The Fantasy Economy: Neoliberalism, Inequality, and the Education Reform Movement by Jocelyn Wills